2017
DOI: 10.1136/heartjnl-2016-310812
|View full text |Cite|
|
Sign up to set email alerts
|

Renal resistive index reflects Fontan pathophysiology and predicts mortality

Abstract: The RRI reflected heart failure severity, hepatorenal function and glucose intolerance, and predicted all-cause mortality in Fontan patients. Therefore, the RRI may be a useful marker of Fontan-associated multiorgan pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…After completion of the Fontan operation, elevated venous pressure and low cardiac output may contribute further to chronic renal dysfunction [308]. End-stage Fontan failure is characterised by a cardio-hepato-renal interaction, and it is possible that the contribution of the kidneys to this pathological process has been underestimated [309].…”
Section: Postulated Pathophysiologymentioning
confidence: 99%
“…After completion of the Fontan operation, elevated venous pressure and low cardiac output may contribute further to chronic renal dysfunction [308]. End-stage Fontan failure is characterised by a cardio-hepato-renal interaction, and it is possible that the contribution of the kidneys to this pathological process has been underestimated [309].…”
Section: Postulated Pathophysiologymentioning
confidence: 99%
“…In addition, because serious post-operative complications, such as supraventricular arrhythmias, PLE, PAVF, and thromboembolic problems often coexist, adaptive mechanisms for maintaining both “appropriate” Rs and the redistribution of limited CO might lead to “failing” and unacceptable pathophysiology. Furthermore, the recent concept of failure can include additional non-cardiac end-organ impairments, such as FALD, 13) 14) 15) 27) renal dysfunction, 12) 27) 28) 29) glucose metabolic abnormalities, 30) and even bone and nutritional problems. 31) 32) Hepato-renal pathophysiology, in particular, has a strong impact on morbidity and mortality in these patients.…”
Section: “Failing” Fontan Circulationmentioning
confidence: 99%
“… 31) 32) Hepato-renal pathophysiology, in particular, has a strong impact on morbidity and mortality in these patients. 14) 29) Thus, these emerging pathophysiologic situations make the definition of “failing” more complex.…”
Section: “Failing” Fontan Circulationmentioning
confidence: 99%
“…Monitoring renal function using US Doppler resistive index is of growing interest as a marker of heart failure and end organ damage in adult congenital heart disease. A recent pediatric Fontan study revealed that a high index >0.81 reflects the severity of heart failure, hepatic and renal function, glucose intolerance and overall mortality [ 69 ].…”
Section: Fontan-associated Liver Diseasementioning
confidence: 99%